KORONER ANJİOPLASTİ UYGULANAN KADIN VE ERKEK HASTA GRUPLARINDA SAPTANAN FARKLI ÖZELLİKLER - DEMİROĞLU, İ.C. Cemşid; AYTEKİN, Vedat; AYTEKİN, Saide; AŞKIN, Hamit K.; TÜFEKÇİOĞLU, Suavi; FERAY, Hasan; DEMİROĞLU, Cem'i (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Female and male patients with coronary artery disease (CAD) have significant differences to each other. To evaluate these differences which lead us to choose the optimal strategy for diagnosis and treatment, we compared some features of female and male patients (pt)s who underwent percutaneous transluminal coronary angioplasty (PTCA) procedure in our interventional cardiology department. Results.- 3400 pts underwent (PTCA) procedure and stent implantation, between years 1991 and 1998. 600 (18%) of the pts were female and 2.800 (82%) were male. Mean age, procedural success rate, risk factors, the location of the lesion in the coronary tree, types of the lesions, restenosis rate and mean values of stent diameters among different pt groups were compared in female and male pts. Mean age values were higher in female pts (female: 59.5±10, male: 54.7±9, p<0.0001). Procedural success rate were nearly same (female: 93.5%, male: 94.5%, p:ns). When we compared the risk factors in a group of 158 pts; hypertension (female: 53.8%, male: 28.7%, p<0.02) and hypercholesterolemia (female: 46.1%, male: 19.6%, p<0.01) were higher in female pts. Diabetes (female: 19%, male: 12%, p: ns), family history of CAD (female: 46%, male: 29%, p: ns) and smoking (female: 23%, male: 39.6%, p: ns) were no more different in two groups. Restenosis rate were 23% in female and 30% in male pts among 308 sequential pts (p: ns). The location of the lesions in the coronary tree (LAD, CXA, RCA) and the types of the lesions (A, B, B2, C) among 1240 sequential pts showed no significant differences between two groups. When we compared the stent diameters of 647 pts, it was lower in female pts than in males (females: 3.18±0.4 mm, males: 3.32± 0.3 mm) (p<0.0001). Conclusion.- Procedural success rate, diabetes, family history of CAD, smoking, re-stenosis rate, the location of the lesions in the coronary tree, the types of the lesions were not significantly different in male and female pts. Mean age values, hypertension and hypercholesterolemia were significantly higher and stent diameter mean value was lower in female pts.